KONTRIBUSI TAMAN PENDIDIKAN QUR’AN NURUL IMAN DALAM PEMBENTUKAN AKHLAKUL KARIMAH ANAK DI DESA KEBON AYU KECAMATAN GERUNG LOMBOK BARAT - Uswatun Hasanah; Muh. Zulkifli; Muhammad Ramdhani Nur (Jurnal Al-Fatih, 2025)
Abstract: This study aims to determine the contribution of the Al-Abror Nurul Iman Quran Education Park (TPQ) in the formation of children's morals in Kebon Ayu Village, Gerung District, West Lombok. The background of this study is the importance of early religious education in forming children's character and morality, especially through non-formal institutions such as TPQ. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that TPQ Al-Abror Nurul Iman not only plays a role in teaching reading and writing the Qur'an, but also provides guidance on moral values through the methods of habituation, role models, and advice. Supporting factors for the formation of noble morals include the involvement of ustadz/ustadzah, parental support, and structured religious activity programs. While inhibiting factors include lack of facilities and infrastructure, limited teaching staff, and the influence of the social environment and media. Thus, TPQ Al-Abror Nurul Iman makes a significant contribution in forming children with noble character amidst the challenges of the times. Keywords: Contribution, TPQ, Formation of Good Morals.